2012
DOI: 10.1016/j.ejogrb.2011.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Headache and adverse pregnancy outcomes: a prospective study

Abstract: Women with headache should be considered at risk for adverse perinatal outcomes and should, therefore, be included in a high-risk pregnancy protocol of care throughout pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
(25 reference statements)
1
23
1
1
Order By: Relevance
“…Another potential confounder is concomitant medication use, particularly in the migraine no‐triptans group. Some of these medications are known to be associated with preterm birth, and depression in particular is often present in patients suffering from migraines …”
Section: Discussionmentioning
confidence: 99%
“…Another potential confounder is concomitant medication use, particularly in the migraine no‐triptans group. Some of these medications are known to be associated with preterm birth, and depression in particular is often present in patients suffering from migraines …”
Section: Discussionmentioning
confidence: 99%
“…Our results largely agree with previous studies examining selected birth outcomes in pregnant women with migraine. Earlier studies found a 1.2‐3.2‐fold increased risk of low birth weight, while results have been contradictory for risks of preterm birth (0.6‐2.7‐fold increased risk), small for gestational age offspring (0.77‐1.07‐fold increased risk), and cesarean delivery (0.94‐1.16‐fold increased risk) . However, only 1 of 5 previous studies found a decreased risk of preterm birth .…”
Section: Discussionmentioning
confidence: 93%
“…2,7,8 Migraine in pregnancy is associated with adverse outcomes in mother and offspring, including pregnancy-associated hypertensive disorders, [9][10][11][12][13] low birth weight, [9][10][11]13,14 and preterm birth. [9][10][11][13][14][15] Associations with other pregnancy and birth outcomes such as placenta previa, gestational diabetes, miscarriage, stillbirth, small for gestational age offspring, cesarean delivery, or birth defects have been less studied. [9][10][11]13,[15][16][17] Nevertheless, most previous studies included fewer than 1000 migraine patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of lifetime prevalence of migraine among pregnant women range from 9–20% (Adeney et al, 2006; Frederick et al, 2014). Several studies have reported higher frequencies of preterm delivery, low birth weight, placental abruption, preeclampsia, and other hypertensive disorders among pregnant migraineurs when compared to pregnant non-migraineurs (Adeney and Williams, 2006; Chen et al, 2010; Marozio et al, 2012; Sanchez et al, 2010; Williams et al, 2011). …”
Section: Introductionmentioning
confidence: 99%